The Effects of Manipulating Symbol Location on Aided AAC Displays : Implications for Display Design - Thistle, Jennifer J.; Cmeyla, Karyn; Holmes, Stephanie; Horn, Maddie; Reum, Alyson (My University, 2018)
Our study explored the relationship between symbol location and preschool children's response time to locate a target symbol. We were specifically interested in the possible development of motor learning as it relates to use of an AAC display.
Color poster with text, images, and graphs.
Keywords: Speech-language pathologists; AAC; Communication disorders; Augmentative and alternative communication; Posters